Beginning JavaScript - McPeak, Jeremy, 1979-; Wilton, Paul, 1969- (Hoboken : Wrox, a Wiley Brand, 2015)
The bestselling JavaScript guide, updated with current features and best practices Beginning JavaScript 5th Edition shows you how to work effectively with JavaScript frameworks, functions, and modern browsers, and teaches more effective coding practices using HTML5. This new edition has been extensively updated to reflect the way JavaScript is most commonly used today, introducing you to the latest tools and techniques available to JavaScript developers. Coverage includes modern coding practices using HTML5 markup, the JSON data format, DOM APIs, the jQuery framework, and more. Exercises with solutions provide plenty of opportunity to practice, and the companion website offers downloadable code for all examples given in the book.-Learn JavaScript using the most up to date coding style -Understand JSON, functions, events, and feature detection -Utilize the new HTML5 elements and the related API -Explore new features including geolocation, local storage, and more JavaScript has shaped the Web from a passive medium into one that is rich, dynamic, and interactive. No matter the technology on the server side, it's JavaScript that makes it come alive in the browser. To learn JavaScript the way it's used today, Beginning JavaScript, 5th Edition is your concise guide.
Introduction to JavaScript and the Web -- Data Types and Variables -- Decisions and Loops -- Functions and Scope -- JavaScript: An Object-Based Language -- String Manipulation -- Date, Time, and Timers -- Programming the Browser -- DOM Scripting -- Events -- HTML Forms: Interacting with the User -- JSON -- Data Storage -- Ajax -- HTML5 Media -- jQuery -- Other JavaScript Libraries -- Common Mistakes, Debugging, and Error Handling -- Answers to Exercises -- JavaScript Core Reference -- W3C DOM Reference -- Latin-1 Character Set.
Includes index.
Vendor-supplied metadata.
Keywords: JavaScript (Computer program language); World Wide Web; Web servers; Electronic books